Analisis Kesulitan Belajar Siswa SMP 01 Bengkulu Tengah Kelas VII Melalui Diagnotik pada Penyajian Data - Paramis Wari, Cicik; Syntia Monica, Debby; Fitri Ramadani, Wulan (JPT : Jurnal Pendidikan Tematik, 2020)
This study aims to describe the learning difficulties of seventh grade students of SMP 01 Bengkulu Tengah in data presentation subjects as seen from the location, type and factors that cause student learning difficulties. This type of research is descriptive research. The research subjects were students of SMP 01 Bengkulu Tengah, grade VII, whose mathematics subject was the subject of data presentation, totaling 5 people. The research instrument developed to collect data in this study was a test. From the results of the research conducted, it was obtained: the types of learning difficulties experienced by students in the material on the data presentation subject were the types of procedural errors (skills) and facts with the respective percentages of 5% and 19%. Therefore, it is very important for students to understand and master the material facts and understand the procedures (skills) that are carried out in solving the problems given.